Improved Round Robin CPU scheduling algorithm: Round Robin, Shortest Job First and priority algorithm coupled to increase throughput and decrease waiting time and turnaround time - Parekh, Harshal Bharatkumar; Chaudhari, Sheetal (ICGTSPICC 2016 : proceedings : International Conference on Global Trends in Signal Processing, Information Computing and Communication : 22-24 December 2016, Jalgaon, India, 2016)
In multitasking operating system, processes don't run simultaneously, but switch very expeditiously. Thus, all the processes share the CPU time. It is the job of the scheduler to select a process from the ready queue and place it into the memory based a particular strategy known as Scheduling Algorithm. There exist many Scheduling Algorithms such as First Come First Serve (FCFS), Shortest Job First (SJF), Round Robin (RR), Priority Scheduling, Multilevel Queue Scheduling (MLQ). This paper proposes a new strategy consolidating three of the existing scheduling algorithms to create a new strategy that reduces the time a process spends in waiting state. The proposed algorithm also reduces the number of context switches to provide a fair, efficient and methodical scheduling algorithm. The algorithm is an extended version of Round Robin Algorithm where each of the processes is given a priority level (low, medium or high) and based on the priority level, the Time Quantum for that process is decided and executed. The throughput of the algorithm is increased by executing processes with smaller burst time or smaller remaining burst time by allocating the process to the CPU as soon as it is ready but not pre-empting the running process.